INTERPRETASI MAKNA SAPAAN MAS TERHADAP ETNIK JAWA DI MAKASSAR (STUDI KOMUNIKASI ANTAR-BUDAYA DI MAKASSAR) - Sunani, Ulya (Al-Mishbah: Jurnal Ilmu Dakwah dan Komunikasi, 2020)
One of the Javanese ethnic identities present in Makassar is called Mas for male Javanese. This nickname has been going on for a long time and it is not yet known exactly when it began, with a span of time, then the identity of Mas has become the property of Javanese men in Sulawesi, especially Makassar. The two ethnic groups in Makassar, namely; ethnic outside of Java and Javanese have the same usage of Mas , namely; is a greeting to pay respect to others and as a door of intimacy to people who have not known their identity, especially for traders, Mas greetings are common, but the problem is the application and generalization of Javanese ethnic in Makassar